Native atrial septal restriction after Fontan palliation successfully treated with transcatheter Diabolo stent - Osamah Aldoss; Benjamin E Reinking; Abhay Divekar (Wolters Kluwer Medknow Publications, 2016)
A 6-year-old male child born with hypoplastic left heart syndrome (HLHS) was palliated with an extracardiac nonfenestrated Fontan procedure (18-mm Gore-Tex tube graft). He developed low-pressure (mean Fontan pressure 10 mmHg) protein-losing enteropathy 6 months after Fontan palliation. After initially responding to medical therapy and transcatheter pulmonary artery stent implantation, he developed medically refractory protein-losing enteropathy. At this time, his transthoracic echocardiogram showed new restriction across his native atrial septum with an 8 mmHg mean gradient. Cardiac catheterization now showed high-pressure (mean Fontan pressure 18-20 mmHg) protein-losing enteropathy and a new 6 mmHg mean gradient across the atrial septum. To avoid cardiopulmonary bypass, he underwent successful transcatheter relief of atrial septal restriction and creation of a fenestration with rapid clinical and biochemical improvement of his protein-losing enteropathy.